PENGARUH JUMLAH UANG BEREDAR (JUB) DAN EKSPOR TEMBAKAU TERHADAP KURS DI INDONESIA - Siti Aryani; Murtala Murtala (LPPM UNIMAL, 2019)
This study aims to determine the effect of the money supply and export of tobacco on the exchange rate in Indonesia. This study uses time series data from 1986 to 2016. To analyze data, this uses Multiple linear regression and Vector Autoregression Model (VAR). Based on the results of the study obtained, it can be seen that partially the money supply had a positive and significant effect on the exchange rate and the export of tobacco had a negative and significant effect on the exchange rate. While simultaneously, the money supply and exports of tobacco had a positive and significant effect on the exchange rate in Indonesia. Furthermore, the results of the VAR analysis model showed that the exchange rate why influenced significantly and positively by the movement itself. The money supply had a positive and insignificant effect on the exchange rate while tobacco exports had a positive and significant effect on the exchange rate.